Growth and health status of children and adolescents in medieval Central Europe - Krenz-Niedbała, Marta (Anthropological Review, 2017)
Subadult growth and health have been analyzed in three cemetery samples from medieval Poland, including two early-urban sites: Cedynia dated to the 10t–14th centuries AD, and Ostrów Lednicki dated to the 13th–15th centuries AD, and a rural site Słaboszewo dated to the 14th–17th centuries AD. The nutritional status was not expected to have substantially differed among the settlements, due to the culturally induced undiversified diet of children, and predominant share of medium-to-low status individuals. However, city life and village life were supposed to differ in factors correlated with the spread of infections, and as such it was expected to find significant differences in respiratory health among early-urban and rural dwellers.The prevalences of diet-dependent diseases, scurvy and rickets, were found to be statistically indistinguishable among the three studied populations, while higher frequency of skeletal signs of poor respiratory health was observed in early-urban Cedynia than rural Słaboszewo. Slightly lower prevalences of skeletal stress indicators were found for the rural than the early-urban site. Skeletal growth profiles and the dynamics of long bone growth were found to be remarkably similar for the early-urban samples (Cedynia and Ostrów Lednicki), with the rural subadults having the shortest diaphyseal lengths, and lower growth dynamics.It can be concluded that adverse factors associated with the urban settlement were more detrimental to respiratory health than those in the village. A variety of factors are potentially responsible for this pattern, including population density, building structure, quality of air and water, sanitation, and occupation. Perhaps, the key factor in response to environmental and socio-cultural constraints was the stability of living conditions in the village, which allowed the inhabitants to develop sufficient adaptive mechanisms. In contrast, the history of strongholds such as Cedynia was changeable due to political situation, military threats and migrations of people.